Implementasi e-Faktur terhadap Kepatuhan Pengusaha Kena Pajak dalam Pelaporan SPT Masa PPn : Implementasi e-Faktur terhadap Kepatuhan Pengusaha Kena Pajak dalam Pelaporan SPT Masa PPn - Rolia Wahasusmiah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
The purpose of this study was to analyze the application of the e-Faktur application to taxable entrepreneurs in terms of reporting VAT Periodic Returns, as well as to see the level of compliance of taxable entrepreneurs registered at KPP Pratama Seberang Ulu Palembang. The research method used is descriptive method and data collection techniques used are documentation and interviews. The sources of data in this study are the number of registered Taxable Entrepreneurs, the number of Taxable Entrepreneurs who use e-Faktur, and the number of SPT Periodic VAT received from 2015 to 2019. The results of the study show that the level of compliance of taxable entrepreneurs using the e-invoice application has been effective, it can be seen that almost all Taxable Entrepreneurs have activated it the tax e-invoice application, but the implementation of the e-invoice application which has been effective is not accompanied by the compliance of taxable entrepreneurs which actually decreases after the mandatory use of the e-invoice application.